PERAN PENYULUH PERIKANAN DALAM MEMBINA KELOMPOK PELESTARIAN HUTAN MANGROVE DI DESA MUARA PANTUAN KECAMATAN ANGGANA KABUPATEN KUTAI KARTANEGARA - Anuar Riduansyah; Helminuddin; Fitriyana (2339-1324, 2022)
This research was performed to know the Role of Fishery Extension Agent in Supervising Mangrove Forest Preservation Group in Muara Pantuan Village Anggana Sub-District Kutai Kartanegara District. Primary data were collected in November 2019 in Muara Pantuan Village Anggana Sub-District Kutai Kartanegara District through interview using question list arranged in accordance with the research objectives. Sampling method used was census method, obtaining 36 people of mangrove forest preservation group, who were all chosen as the research respondents. The data were further analyzed through descriptive quantitative. Direct interview was also done receiving respondents answers of questionnaire provided, which was then analyzed through scoring method. Research method showed that the roles of extension agent as a communicator, facilitator, and mediator were strong, while their role as organizer was decent. Furthermore, regarding the perception of mangrove forest preservation group, the role of fishery extension agent in Muara Pantuan Vilage was overall strong with the mean score of 40.1 at the range of 35.2 – 45.0.